الميول المهنية لدى تلاميذ المستويات الدراسية المعنية بعملية التوجيه المدرسي - صالحي، فاطمة (جامعة الوادي university of Eloued, 2017)
ملخص الدراسة : يبحث موضوع الدراسة في استكشاف الميول المهنية لدى تلاميذ المستويات الدراسية المعنية بعملية التوجيه المدرسي (الثالثة متوسط ، الرابعة متوسط ، الأولى ثانوي ) ومدى تأثرها بمجموعة من المتغيرات التصنيفية كالجنس و السن والمستوى الدراسي و المستوى التحصيلي و المستوى الاقتصادي للأسرة و المستوى التعليمي للوالدين . وقد شملت عينة الدراسة على ( 118تلميذا) من تلاميذ(السنة ثالثة و الرابعة متوسط) من متوسطة آل ياسر _الرباح _ الوادي ، وتلاميذ السنة الأولى ثانوي من الجذعين المشتركين من ثانوية لقرع محمد الضيف _ الرباح _ الوادي. تم الاعتماد في هذه الدراسة على المنهج التتبعي المستعرض . وأستخدم الباحث المقاييس التالية : مقياس المستوى الميول المهنية " لجون هولاند " المعدل على البيئة الجزائرية ، وأستخدم كذلك مقياس " عمار الهوارنة " للمستوى الاقتصادي الاجتماعي الثقافي للأسرة . و لمعالجة فرضيات الدراسة قد أستخدم الأساليب الإحصائية التالية: تقنيات الإحصاء الوصفي : التكرارات ، النسب المئوية ، الانحراف المعياري ، معامل الارتباط. تقنيات الإحصاء الاستدلالي : اختبار "ت" لقياس متوسط الفروق ،"ألفا كرونباخ" اختبار "ف" لتحليل التباين ، اختبار "شيفي" للمقارنة المتعددة ، ونشير إلى أنه تم استخدام البرنامج الآلي للمعالجة اإححصائية للمعطيات" "spssلاستخراج النتائج، حيث توصل الباحث إلى أن3 الميل المهني السائد بين تلاميذ العينة هو الميل نحو المهن الفنية ، وعدم وجود فروق دالة إحصائيا في الميول المهنية لدى تلاميذ عينة الدراسة. وكذلك لم يجد الباحث فروق في الميول المهنية بين تلاميذ العينة تبعا للمتغيرات التصنيفية التالية (الجنس، السن ، المستوى الاقتصادي للأسرة و المستوى التحصيلي و المستوى التعليمي للوادين Study Summary: The subject of the study is to explore the professional orientation of the students in the study levels concerned with the school orientation process (third and fourth year middle school and secondary school) The objectif of this study is to know the professional tendencies of the students in the educational levels in the school guidance process and the extent to which these professional tendencies are affected by a range of taxonomic variables such as gender, age, level of education, the level of achievement, the economic level of the family and the educational level of the parents. The study sample consisted of (118) male and female pupils in the three levels of study (third and fourth years) from the middle of Al-Yasser Robbah EL OUED, and the first-year secondary students of the common roots (common trunk of science and technology and common trunk etiquette) Mohammed Al-Dheif _ Robbah EL OUED. The revised tracking approach has been followed. John Halland's revised professional level scale has been applied to the Algerian environment, and the Ammar Al-Hawarneh scale has also been used for the socio-economic and cultural level of the family. To address the hypotheses of the study, the following statistical methods were used: Techniques of descriptive statistics: frequencies, percentages, standard deviation, correlation coefficient. Methods of Inductive Statistics: T-Test for Mean Difference, Alpha Kronbach, P-Test for Contrast Analysis, Shivi Test for Multiple Comparison, and we note that the Statistical Data Processing Program (SPSS) was used to extract the results. Indicates that the predominant occupational tendency among the sample students is the tendency towards the professional professions, the absence of statistically significant differences in the professional orientation of the students in the study levels concerned with the school guidance process (third and fourth year middle school and secondary school). The researcher also did not find differences in the professional orientation among the students according to the following taxonomic variables (gender, age, economic level of the family, achievement level and educational level of the students .
دراسة تتبعيه مستعرضة بمتوسطة آل ياسر – ثانوية لقرع محمد الضيف – -بالرباح ولاية الوادي
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: الميول المهنية، التوجيه المدرسي و المهني، مناهج التوجيه; Orientation professionnelle, orientation scolaire et professionnelle, programmes d'orientation; Professional orientation, school and vocational guidance, guidance curricula